MAKNA DUA CINTA: ANTARA KELUARGA DAN TANAH AIR - Tameon, Irmina H (Humanis, 2013)
Object of this research is novel Tanah Air Beta, written by Sefryana Khairil. The novel Tanah Air Beta was analyzed with literary sociology approach. The issues raised in this research are (1) How the characters, plot, and setting in the novel Tanah Air Beta, (2) How the literary sociology aspects revealed in the novel Tanah Air Beta. The theories applied in this research are the theory of structure and Literature Sociology. The result of this research indicates that the societies of ex-Timor Leste have sense of deep love to Indonesian as their motherland and to their family.
Keywords: personality, development, sociology